Pemanfatan Bekas Spesi Untuk Pembuatan Spesi Baru - Aji, Seno; Arif Bakhtiar E, Moh (JURNAL AGRI-TEK, 2014)
Generally, building residential or construction of buildings in indonesia using walls of masonry red both in finishing with stucco or without stucco. Aim of this study to determine the compressive strength value uses a new specie of the former specie aggregate results dismantling the wall and to determine the compressive strength value of comparison with the new specie aggregate (using natural sand aggregate Ngraho Bojonegoro). Specie siar recycle used in this study contains material was red brick, sand, red cement, lime and cement. Ingredient for all specie that used on the specimen testing using a ratio of 1 PC : 5 sand. the compressive strength value testing using a sample of a cube measuring 150 mm x 150 mm x 150 mm with 3 variations of the sample is 0% (without the former specie), 50% (with 50% of the former specie) and 100% (100% with the new specie using natural sand aggregate Ngraho Bojonegoro). the compressive strength value of Species from the recycle specie qualify as specie type O, with a minimum compressive.strength.value.is.24,5.kg/cm2.Key words : new specie, the former specie, species of siar, the compressive strength value.